2006
DOI: 10.3346/jkms.2006.21.6.1028
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Evolution of Anemia Associated with Tuberculosis

Abstract: Tuberculosis (TB) may produce abnormalities in the peripheral blood, including anemia. However, the evolution of TB-associated anemia with short-term combination anti-TB chemotherapy has not been well elucidated. The aim of this study was to characterize TB-associated anemia by clarifying its prevalence, characteristics, and evolution, through involving large numbers of patients with TB. The medical records of adult patients with TB diagnosed between June 2000 and May 2001 were reviewed. Among 880 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
105
8
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(149 citation statements)
references
References 21 publications
(23 reference statements)
29
105
8
7
Order By: Relevance
“…Anemia is a common hematologic complication among TB patients and is a strong risk factor for mortality [11]. In one study the prevalence of anemia among tuberculosis patients was reported to be 31.9 % [12]. Previous studies in sub-Saharan Africa also found a high prevalence of anemia; 88 % of HIV-positive and 77 % of HIV-negative TB patients were anaemic in Malawi [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is a common hematologic complication among TB patients and is a strong risk factor for mortality [11]. In one study the prevalence of anemia among tuberculosis patients was reported to be 31.9 % [12]. Previous studies in sub-Saharan Africa also found a high prevalence of anemia; 88 % of HIV-positive and 77 % of HIV-negative TB patients were anaemic in Malawi [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of TB-associated anemia varies from 32% to 86% [5] [6] [7] and numerous causes have been invoked [8]. It should be noted that anemia in tuberculosis is mainly inflammatory anemia (anemia of inflammation or AI).…”
Section: Introductionmentioning
confidence: 99%
“…Anemia is widely recognized as a common TB-associated morbidity [4] [5]. The prevalence of TB-associated anemia varies from 32% to 86% [5] [6] [7] and numerous causes have been invoked [8].…”
Section: Introductionmentioning
confidence: 99%
“…Bunların başlıcaları; anemi, artmış eritrosit sedimentasyon hızı, düşük serum albumin düzeyi, hiponatremi, anormal karaciğer enzim düzeyleri, lökositoz ve hipokalsemidir. [20] Hastaların laboratuvar incelemesinde; lökositoz, anemi, hiponatremi, hipoalbuminemi, anormal karaciğer enzim düzeyleri ve hipokalsemi görülmedi ancak eritrosit sedimentasyon hızı ortalaması normal üst sınırın üzerinde idi.…”
Section: Discussionunclassified